The root and tuber crops program at CARDI - Forde, S.C. (International Center for Tropical Agriculture, 1986)
The research, training, and development activities related to sweet potato, yam, cassava, and aroids, carried out by the root crop program of the Caribbean Agricultural Research and Development Institute (Trinidad and Tobago), are presented. The present interest in cassava is its use as a maize substitute in animal feeds. The following activities are in progress: introduction and evaluation of CIAT cv. in multilocational trials; study of selected cassava lines resistant to CBB; development of improved cassava production through mechanized systems of planting and harvesting, and fertilizer and herbicide application; development of systems for chipping and drying cassava for use in animal feeds. (CIAT)